Coherent photon-phonon conversion in integrated circuits - Stiller, Birgit; Merklein, Moritz; Eggleton, Benjamin J. (Optics InfoBase Conference Papers, 2017)
We experimentally demonstrate multiple conversions of information between the optical and acoustic domain. We show the coherent acousto-optic transfer by retrieving multiple amplitude and phase levels with GHz bandwidth and demonstrate multi-wavelength operation.
CRIS-Team Scopus Importer:2021-06-29